Sistem Informasi Manajemen Pemesanan Dan Penjualan Pada UNDIP Distro - Mohammad Dwi Cahyono; Kodrat Iman Satoto; Rinta Kridalukmana (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2015)
At present time, information technology facilitates business very well. The eases provided by technology will attract many consumers. However, a middle level company such as UNDIP Distro is rarely found providing neither the ease of shopping or online ordering service. Therefore, web based system is needed by UNDIP Distro company in order to facilitate the owner and the admin to manage the sale, service, and marketing and the customer’s shopping Sistem Informasi Manajemen Penjualan dan Pemasaran UNDIP Distro is a web based application made using PHP program language in scope of Framework Code Igniter and basic data of MySQL. The development method used is waterfall method. Information system modeling in application plan was built using UML modeling. The result of the application plan is a web based application that can manage data in UNDIP Distro such as products, orders, and members data.